2022
DOI: 10.3389/fendo.2022.768363
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Autoimmunity in Female Infertility and Assisted Reproductive Technology Outcome

Abstract: The regulation of the female reproductive system is one of the most relevant actions of thyroid hormones. Adequate thyroid hormones production is essential for normal menstrual function and fertility as well as for the successful maintenance of pregnancy. The relationship between reproductive failure and thyroid disorders is particularly relevant and attracts attention worldwide. Thyroid autoimmunity (TAI), defined by the presence of circulating antithyroid antibodies targeting thyroid peroxidase (TPOAb) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 99 publications
1
18
0
2
Order By: Relevance
“…A total of 13 (7.3%) participants received ART in our study. Receiving ART was closely linked to the adverse neonatal outcome such as preterm birth and low birth weight in our study, which was consistent with previous report ( 8 , 19 , 33 ). Previous cohort or clinical trials showed that levothyroxine (LT4) intervention for euthyroid women with positive TPOAb did not improve the pregnancy outcome ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 93%
“…A total of 13 (7.3%) participants received ART in our study. Receiving ART was closely linked to the adverse neonatal outcome such as preterm birth and low birth weight in our study, which was consistent with previous report ( 8 , 19 , 33 ). Previous cohort or clinical trials showed that levothyroxine (LT4) intervention for euthyroid women with positive TPOAb did not improve the pregnancy outcome ( 34 , 35 ).…”
Section: Discussionsupporting
confidence: 93%
“…Despite serum TPO‐Ab levels providing high predictive value for early diagnosis of autoimmune thyroid disease, 12% to 26% people with normal thyroid function may have high level of TPO‐Ab, accompanied by elevation of thyroid stimulating hormone (TSH) level in thyroid tissue (Abbassi‐Ghanavati et al, 2010; Bucci et al, 2022). In pregnancy, a high TSH level was associated with preterm delivery and MR (Du et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In our literature search, 6 literatures defined the positivity of TAI by the presence of either TPO‐Ab or TG‐Ab, so we excluded them for our meta‐analysis. Nevertheless, the presence of TG‐Ab along with TPO‐Ab were also found in 10% of infertile patients (Al‐Saab & Haddad, 2014; Bucci et al, 2022). TG‐Ab may diminish the ovarian reserve together with TPO‐Ab to influence pregnancy outcome (Wu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A systemic imbalance of helper lymphocyte Th1/Th2/Th17 and Treg activity, leading to increased secretion of inflammatory cytokines interleukin (Il)-2, IL-17, and interferon-γ (INF-γ)—known factors of implantation failure and pregnancy loss—was observed in women with TAI ( 24 , 25 ). In addition, excessive activation and cytotoxicity of natural killer (NK) cells in peripheral blood and the uterus, as well as upregulation of NKT-like cells, have been reported ( 26 28 ). Interestingly, NK cell numbers and activity can be enhanced not only by Il-2 and INF-γ but also by TSH acting in an endocrine and paracrine manner ( 17 ).…”
Section: Pathophysiologymentioning
confidence: 99%